“Stick Time”: on the role of emotional and symbolic rewards in the etiology of police violence - Brezina, Timothy (Journal of Theoretical and Philosophical Criminology, 2024)
In the United States, the problem of police violence is frequently interpreted as a symptom of an underlying deficit, such as a lack of proper police officer training in the use of force; failure to adopt procedural justice strategies; or lack of preparation, coordination, and proper technique when responding to crowds. In this paper, the complex nature of police violence is examined from a different angle. Drawing on theory and research on non-social reinforcement, appetitive aggression, and the phenomenological foreground of violent behavior, we explore the possibility that some police officers are attracted to aggressive confrontation and that, for these officers, the use of force is associated with emotional and symbolic rewards. Further, these officers may organize their activities in pursuit of such rewards. Selected case studies are presented to illustrate these ideas. Finally, we explore the conditions that may influence the attraction to aggressive confrontation and discuss implications for police reform.